140k views
5 votes
Need Help ASAP

Formula 1 can be written alternatively as formula 2. Use algebra to show your steps how formula 1 can be manipulated to create formula 2.


Formula 1:


f(n)=\left\\ ({\sqrt[{12}]{2}}\,\right)^(n-49)* 440\,{\text{Hz}}\,}


Formula 2:


f(n) = 440 (2)^{(n-49)/(12) }

User Kaya
by
4.7k points

1 Answer

2 votes

Answer:

Steps are shown

Explanation:

Exponent Rules

We need to recall this fundamental rule for exponents:


\displaystyle \sqrt[n]{a^m}=a^(m/n)

We are given the expression:


f(n)=\left ({\sqrt[{12}]{2}}\,\right)^(n-49)* 440\,{\text{Hz}}

We'll use algebra and the above rule to manipulate the expression.

First, get rid of the unit Hz and move the coefficient 440 to the left:


f(n)=440\left ({\sqrt[{12}]{2}}\,\right)^(n-49)

Now we convert the radical into an exponent form:


\displaystyle \left ({\sqrt[{12}]{2}}\,\right)^(n-49)=(2)^{(n-49)/(12)}

Substitute:


f(n)=440\left ({\sqrt[{12}]{2}}\,\right)^(n-49)=440~(2)^{(n-49)/(12)}

This is the very same expression in formula 2, as required.

User Ronan Boiteau
by
4.7k points